Usaha Peningkatan Daya Dukung Tanah Lempung Menggunakan Layer Krikil, Anyaman Bambu dan Kombinasi Kolom-Layer Pasir - Dian Eksana Wibowo; Hermawan Wahyu Rahmadianto; Endaryanta Endaryanta (Universitas Negeri Yogyakarta, 2021)
ABSTRACT Clay soil is soil that has a low value of pressure strength and bearing capacity. The purpose of this study is using a layer of gravel, woven bamboo, and a combination of column-layer sand as an alternative to improve the carrying capacity of clay soil, then the results from the tests are compared with each other. The method in this study is experimental. The samples of soil were taken from Kalangan, Kasihan, Bantul, D.I. Yogyakarta. The foundation soil model using steel tub size 100x100x40 cm, with soil volume 100x100x30 cm. Soil loading uses steel plates that are loaded with hydraulic jacks, equipped with a proving ring as a load reader. The column-layer combination consists of 3 sand layers, 1 cm thick horizontal position and 5 cm spacing between layers. The sand column is 1 cm in diameter with a hole depth of 20 cm. The gravel layer pattern consists of 3 layers of gravel with a layer thickness of 2 cm, the distance between the layers is 5 cm. Woven bamboo pattern: 1 layer with a length of 20x20 cm. Placement of woven bamboo at a depth of 2 cm from the ground. The results of the research are; (1) The Soil is a high plasticity (CH) inorganic clay based on the USCS system, including the medium to poor clay soil group (A-7-6 (40)) based on the AASHTO system. (2) The Strengthening of gravel layer increases the ultimate bearing capacity by 2.5 times or 159.02%, while bamboo matting provides an increase in bearing capacity by 2.7 times or 170.49%, and the combination of column-layer sand by 2.2 times. or 127, 87%. (3) The reinforcement of bamboo mats provides the highest increase in bearing capacity in clay soil between the gravel layer and the combined reinforcement of the sand column and the sand layer. This shows that the use of woven bamboo is more effective as a material for strengthening clay. ABSTRAKTanah lempung adalah tanah yang mempunyai nilai kekuatan tekanan serta nilai daya dukung rendah. Tujuan penelitian ini adalah penggunaan layer kerikil, anyaman bambu, dan kombinasi kolom-layer pasir sebagai alternatif perbaikan peningkatan daya dukung tanah lempung, kemudian hasil dari pengujian dibandingkan satu sama lain. Metode yang digunakan adalah experimen. Sampel tanah diambil dari Kalangan, Kasihan, Bantul, D.I. Yogyakarta. Pemodelan tanah pondasi menggunakan bak baja ukuran 100x100x40cm, volume tanah 100x100x30cm. Pembebanan tanah menggunakan pelat baja yang dibebani dengan dongkrak hidrolik, dilengkapi proving ring sebagai pembaca beban. Kombinasi kolom-layer pasir terdiri dari 3 lapis pasir, posisi horizontal tebal 1 cm dan jarak antar lapisan 5 cm. Kolom pasir diamter 1 cm dengan kedalaman lubang 20 cm. Pola layer kerikil terdiri 3 lapis kerikil dengan ketebalan lapisan 2 cm, jarak antar lapisan 5 cm. Pola anyaman bambu:1 lapis dengan panjang-lebar anyaman 20x20 cm. Penempatan anyaman bambu pada kedalaman 2 cm dari permukaan tanah. Hasil penelitian yaitu ; (1) Tanah merupakan tanah lempung anorganik plastisitas tinggi (CH) berdasarkan sistem USCS, termasuk kelompok tanah berlempung kualitas sedang sampai buruk (A-7-6(40)) berdasarkan sistem AASHTO. (2) Perkuatan layer kerikil meningkatkan daya dukung ultimit sebesar 2,5 kali atau 159,02 %, sedangkan anyaman bambu memberikan peningkatan daya dukung sebesar 2,7 kali atau 170,49 %, dan kombinasi kolom-layer pasir sebesar 2,2 kali atau 127, 87%. (3) Perkuatan anyaman bambu memberikan peningkatan daya dukung paling tinggi pada tanah lempung diantara bahan perkuatan layer kerikil dan perkuatan gabungan kolom pasir dan layer pasir. Hal ini menunjukkan bahwa penggunaan anyaman bambu lebih efektif sebagai bahan perkuatan tanah lempung.